Factors for good neurological outcome in adult OHCA with initial shockable rhythm: a retrospective multicenter cohort study from the German Resuscitation Registry - Stephan Katzenschlager; Nikolai Kaltschmidt; Simon Orlob; Frank Weilbacher; Matthias Huck; Stephan Seewald; Lisa Rück; Hanna Hoffmann; Erik Popp; Jan-Thorsten Gräsner; Jan Wnent (Resuscitation Plus, 2025)
Study aim: This study examined defibrillation attempts during out-of-hospital cardiac arrest (OHCA) with shockable rhythm and survival outcomes, focusing on good neurological outcome at discharge. It aimed to identify predictors of favorable outcomes and guide future trials for alternative defibrillation strategies. Methods: In this retrospective, multicenter cohort study, data were extracted from the German Resuscitation Registry for adult patients (≥18 years) who experienced OHCA with an initial shockable rhythm between January 2007 and December 2023. Only cases from good data quality centers were included. Patients were categorized according to the number of defibrillations received (1, 2–3, 4–6, and ≥7). Multivariable logistic regression was performed to identify independent predictors of favorable neurological outcomes. Results: Out of 332,001 OHCA records, 15,284 met the inclusion criteria. Survival endpoints, including any return of spontaneous circulation, hospital admission with ROSC, 24-h survival, and survival to discharge, significantly declined with an increasing number of defibrillation attempts. In the regression analysis, EMS-witnessed arrests were strongly associated with favorable outcomes (OR 3.8; 95 % Confidence Interval 3.1–4.7). More defibrillations, prolonged ambulance response times, and older age were independently associated with lower odds of achieving a favorable neurological outcome. Conclusion: An increasing number of defibrillations is independently linked to reduced survival and worse neurological outcomes in adults experiencing out-of-hospital cardiac arrest with an initial shockable rhythm. These results underscore the urgent need for alternative management strategies for multiple defibrillation attempts. These compelling observations warrant a reevaluation of defibrillation protocols to improve patient outcomes.